Perancangan Aplikasi Task Management Untuk Asisten Laboratorium Dengan Metode PIECES Berbasis Android - Rima Tamara Aldisa; Muhammad Naufal Rifqi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to build a task management application aimed at laboratory assistants to plan and develop a job in one period. With this android-based application, it is easier for laboratory assistants to be able to find out more about how satisfied and comfortable the assistant is in using the application. This system is made using the Pieces method, with measurements of 6 aspects or variables, namely from the aspects of Performance, Information, Economics, Control, Effeciency, Service. The results of the analysis of the Pieces method show that the measurement of the satisfaction level of the system is laboratory assistant. With a method that produces an average value of 3.518 and is included in the satisfactory category, it can be said that the use of this application helps the laboratory during a period of being satisfied with the android-based application.